Aplicativo web de aprendizaje para el desarrollo de destrezas para estudiantes con necesidades educativas especiales con discapacidad auditiva en el sistema educativo del Cantón La Maná. - Chávez Ortiz, Jailanderw Vinicio (2021)
This research project was carried out with the collaboration of the La Maná Educational Unit of the Cantón “La Maná”, Cotopaxi province, as a function of supporting the education of hearing impaired students, taking the processes of teachings that are carried out in manual forms , didactic cards for which only these tools count for future student performance, for this reason our objective is to implement a web application of information articles with the purpose of disseminating systematic pedagogical support tools in favor of increasing the listening skills of children, deaf youth who attend the educational system. In order to know the teaching process of the La Maná Educational Unit, surveys were carried out to the order of the director who is the DECE department "Student Counseling Department", to identify the needs of the problem and collect the requirements. The MVC architecture was also applied, with the help of the Content Manager CMS in conjunction with the WordPress Tool and the working style of the Scrum methodology in the web environment. Unified Modeling Language (UML) for the elaboration of use case diagrams, class diagrams. The web application consists of a registry of Users registered to the website and you will be able to view content published on our blog page that will have downloadable text, multimedia, links, embedded game content, it will have a post form that you can publish on our blog. Resulting in the site of Pedagogical Support for Hearing Disability with the information management Department DECE of the La Maná Educational Unit. Which responds to specific needs, allowing him to support students, teachers, parents in an environment of greater completion of the hearing impairment in publicizing techniques, tools, applications and forms of communication in future knowledge.